Technical report: solving Biharmonic equation of linear analysis of thin plates by using Finite Difference Method / Nurul Husna Sulaiman and Haziera Mohd Termizi - Sulaiman, Nurul Husna; Mohd Termizi, Haziera (2018)
This report addresses the problem to learn the values of deflection at nodal points of adopted network by solving Biharmonic equation using Finite Difference Method (FDM). Biharmonic equation is a fourth order partial differential equation for continuum mechanism of linear elasticity of thin plate. By varying loads on thin plate, it will give different values of deflection at each nodes. To present these results, the Biharmonic equation is discretized and solved by using FDM. The deflection is calculated at each nodal points by using MATLAB software. It was found that the more loads is placed on thin plate, the higher the values of deflection at each nodes obtained. All these results gained were compared with previously published work for validation. It is concluded that FDM can effectively solved these problems of plate deflection, stress, strain and others. In addition, FDM method can be used to solve more complex problems in accordance to the future problems.